FY 2020 Mexico Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2022)
The Country Opinion Survey in Mexico assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Mexico perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Mexico on 1) their views regarding the general environment in Mexico; 2) their overall attitudes toward the WBG in Mexico; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Mexico; and 4) their perceptions of the WBG’s future role in Mexico.